KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA KELOMPOK MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION DAN PROBLEM SOLVING - Arrahim, Arrahim; Dicky Dermawan, Deden (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to determine the significant differences in mathematical problem solving ability between using the Realistic Mathematics Education (RME) model and the Problem Solving model. This study uses a quantitative approach. The research method used is the Quasi Experimental Design research method using the Nonequivalent Pretest Posttest Control Group Design. In experimental class 1 using the Realistic Mathematics Education (RME) model, while experimental class 2 using the Problem Solving model. The sampling technique used Purposive Sampling. The research sample has the same number of students in experimental class 1 and experimental class 2, namely 26 students. The data collection technique used a written test in the form of descriptions. The results showed that the pre-test of experimental class 1 was 44.62, and the post-test was 73.85. Experimental class 2 showed a pre-test of 48.8 and a post-test of 67.69. The t-test analysis obtained a 2-tailed significance value of 0.024 <with a significance level of 0.05, so Ho was rejected and Hi was accepted. This means that there is a significant difference in the ability to solve mathematical problems between using the Realistic Mathematics Education (RME) model and the problem solving model in Class IV of SDN Bojong Menteng 2 Bekasi.